Using an Electronic Text-Matching Tool (Turnitin) to Detect Plagiarism in a New Zealand University - Goddard, R.; Rudzki, R. (Journal of University Teaching and Learning Practice, 2005)
This paper is concerned with reporting the experience and findings of staff using a commercially-available textmatching tool (Turnitin) to detect plagiarism in a university setting in New Zealand. The use of actual instances of plagiarism revealed through Turnitin in a teaching department is a departure from the more usual selfreporting methodology used in many plagiarism research papers. The paper concludes by asking questions of the implications for institutions, teaching staff and students.